Investigation of Raman Amplification In Photonic Crystal Fibers - Fyath, R. S.; Ali Kamil, Zahraa M. (Nahrain University College of Engineering Journal, 2008)
In this paper, Raman amplification characteristics in photonic crystal fibers (PCFs) are investigated in details. Performance comparsion between PCF-based Raman amplifier and other conventional fiber-based counterparts is presented. The simulated results reported here can be used as a guide line todesign PCF-based Raman amplifier that outperforms the conventional fiber amplifiers. Raman gain as high as 33 dB can be obtained with a well designed PCF even at low pump power of 300 mW.